Information needs of key stakeholders with special reference to the role of the press in promoting for food and nutrition in the Caribbean - Gibbings, Wesley (Technical Centre for Agricultural and Rural Cooperation, 2004)
Presentation on theme 2: Information Needs for Improved Decision Making about Food and Nutrition Security